Synthesis and characterization of electrodeposited nickel chalcogenides for photoelectrochemical/ solar cell application - Rajes, K.M.Rajan (2014)
Nickel chalcogenides, NiX2(X=S,Se) thin films were successfully electrodeposited on indium-tin-oxide (ITO)-coated glass substrates. The deposition time for the thin films were set at 10 minutes to 30 minutes with an interval of 5 minutes. The thin films were characterized for their structural, morphological and compositional characteristics. Their optical and semiconducting parameters were also analyzed in order to determine the suitability of the thin films for photoelectrochemical (PEC) / solar cell applications. Films were well adherent to the subtrates and grew up to thickness of ≈ 1.5μm. Structural analysis via X-Ray Diffraction (XRD) analysis reveals that films are polycrystalline with increasing intensity of XRD peaks in thicker films. Preferred orientation of (2 2 0) plane in NiS2 and (2 1 1) plane in NiSe2 was observed as the highest peak in spectrum. The surface morphology of the films determined by Scanning Electron Microscope (SEM) showed the growth of the films to be uniform and well covered for thinner films. However, at longer deposition times, the structure of the films start to break into grains (flakes) due to maximum grain stress point. Compositional analysis via Energy Dispersive X-ray (EDX) technique confirmed the presence of Ni, S, and Se elements in the films synthesized. The optical bandgap energy of the films fit into the range (1-3eV) for a PEC / solar cell materials and decreases as the deposition time of the films increases. Bandgap energy of 1.12 eV and 1.15 eV was obtained for NiS2 and NiSe2 films deposited at 30 minutes and 25 minutes, respectively. Results on the semiconductor parameters analysis of the films showed that the nature of the Mott-Schottky plots indicates that the films obtained are of p-type material. All values come in the range of many other transition metal chalcogenides and this has proven that NiX2(X=S,Se) thin films are capable as a solar / PEC cell material